COMPARISION OF LOCAL ANAESTHETIC POTENTIALS OF DRUGS HAVING MEMBRANE STABILIZING EFFECT ON INFILTRATION ANAESTHESIA IN GUINEA PIGS - Tamma, Navin Kumar; Y, Amar Kumar; Nagakrishna, L; Mishra, S S (Journal of Drug Delivery and Therapeutics, 2013)
Objective : To compare the local anaesthetic action of central neuron sodium channel blockers Phenytoin Sodium, Sodium Valproate and Carbamazepine with peripheral neuron sodium channel blockers Lignocaine using Infiltration anaesthesia in guinea pigs Material and Methods: In the present study,the local anaesthetic effect of Lignocaine with concentration of 0.2%, 0.1% ,0.05% was compared with Phenytoin Sodium, Sodium Valproate and Carbamazepine in concentrations of 0.2%, 0.1% ,0.05% using different dilutions ofÂ 0.05N,0.1N,0.2N HCLÂ in guinea pig by pricking on the skin produces a squeak orÂ movementÂ indicating pain is produced. Results : The results of our present study suggest onset of local anaesthesia with lignocaine 0.2% is significantly fast when compared with concentration of 0.1%, and 0.05% indicating it has better efficacyÂ whenÂ using for variousÂ Â local anaestheticÂ procedures. In addition onset of local anaesthesia with Phenytoin sodium concentrations of 0.2%, 0.1% ,0.05% Â is fast Â when compared with Sodium valproate concentrations of 0.2%, 0.1% ,0.05% Â andÂ Carbamazepine concentrations 0.2%, 0.1% ,0.05%. Conclusion: Among antiepileptic drugs with local anaesthesia and Â membrane stabilizing activity Phenytoin sodium showed fast on set of action when compared with sodium valproate and Carbamazepine indicating it has better efficacy. Keywords : Local Anaesthetics, Membrane Stabilizing, Infiltration anaesthesia.